Rozwój genetyki i nauk żywieniowych a działania na rzecz zachowania zdrowia - Grażyna Nowicka (Studia Ecologiae et Bioethicae, 2005)
Nutrition is a factor of major importance for health and also for development of diet related disorders. Nowadays there is no doubts that interaction between genes and nutrition plays a key role in health risk prediction and disease prevention. Individual nutritional status is determined not only by food availability but also by genes that control food intake, nutrient absorption and metabolism. On the other hand nutrients can significantly influence different genes expression and metabolic processes. Knowledge of genetic susceptibility to disease will help identify people at enhance risk and their response to diet. The prevalence of the types of genes of interest may differ between populations. The same genotype does not confer the same risk in all populations because of differences in environmental factors and nutritional habits. Therefore, populations should not simply copy each other’s dietary recommendations. Based on genetic and nutritional studies the best way for expression of healthier phenotypes should be found and used to promote health and prevent different diseases development.